Studi Kualitatif : Peran Tax Center terhadap Kepatuhan Perpajakan Orang Pribadi Saat Implementasi Regulasi Harmonisasi Peraturan Perpajakan - Imam Agus Faisol; Khy’sh Nusri Leapatra Chamalinda (Politeknik Negeri Bengkalis, 2022)
This research aims to identify and map the role of the Tax Center of the Faculty of Economics and Business, Universitas Trunojoyo Madura (UTM), in fulfilling tax obligations that can increase taxpayer compliance when implementing HPP Law regulations. This research uses qualitative research with a case study approach. Research informants are individual taxpayers involved in tax center activities and active administrators at the FEB UTM Tax Center. The study results indicate that the Tax center has a strategic role as an institution in higher education. One of its visions and missions aligns with the Directorate General of Taxes. In addition to the functions of education, research and community service, the Tax Center is actively involved and participates in the socialization of the latest tax policy, namely the Law on the Harmonisasi Peraturan Perpajakan (HPP). The Tax Centre's existence is crucial considering that the community, especially in universities, requires information and explanations regarding Program Pengungkapan Sukarela (PPS). Enthusiasm and participation in filling out the Annual SPT are part of the indicators of increasing tax compliance in the university environment, as evidenced by the increased participation of taxpayers in filling out the Annual SPT even during the Covid-19 pandemic.